IMPLEMENTASI KONSEP TAUHID SOSIAL M. AMIEN RAIS DI SMA INTERNASIONAL BUDI MULIA DUA YOGYAKARTA - Nurul Hidayah; Suwadi Suwadi (Jurnal Pendidikan Agama Islam, 2015)
Islam religion has been taught to the students since they are in junior high school, but the juvenile delinquency still often happens. Based on M. Amien Rais, social tawhid is needed to be solution of the problem above. Budi Mulia Dua Yogyakarta International Senior High School is one of many schools that is built by M. Amien Rais which has been doing the implementation of the social tauchid concept. Based on M. Amien Rais, social tawhid means a social dimension from tauhīdullāh (to a knowledge the oneness of God). The implementation of the social tawhid concept of M. Amien Rais in Budi Mulia Dua Yogyakarta International Senior High School could be seen from the arrangement of the perspective an the mission of the school. Then it is applied in extracurricular activity and is evaluated by meeting session. Some of the extracurriculars that apply the social tawhid mission are social volunteer, the distribution of Qurban’s meat, tithe institute and flea market.